Organic Photovoltaic Devices: Low Substrate Temperature Encapsulation for Flexible Electrodes and Organic Photovoltaics (Adv. Energy Mater. 6/2015). Issue 6 (March 2015) - Chen, Nan; Kovacik, Peter; Howden, Rachel M.; Wang, Xiaoxue; Lee, Sunghwan; Gleason, Karen K.
<x xml:space="preserve">Abstract</x> In article number 1401442, Karen K. Gleason and co‐workers report a novel bilayer encapsulation strategy based on initiated chemical vapor deposition (iCVD). This damage‐free and solvent‐free method provides conformal and flexible protection to organic photovoltaic devices. For the first time, a vapor‐deposited UV‐screening layer of CeO2 is applied on organic photovoltaics as an encapsulation material. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>